Nova pitekantopoidna oblika hominida iz Severne Afrike - Dolinar Osole, Zlata (Arheološki vestnik, 1956)
W hile system atically excavating the paleolithic site a t T ernifine (O ran, N orth A frica), in June 1954, C. A ram bourg found tw o hom inid m andibles. A ccor[1]ding to the fossil fauna an d to the chelleo-acheulean im plem ents (Cam asian) found in situ, the p e rtin e n t stra tu m could be identified as ea rly Pleistocene. F o r th e first tim e in w orld h isto ry rem ains of the m a k er of the hand-axe cu ltu re w ere found together w ith his tools. The m andibles a re m ost sim ilar to the classic P ithecanthropi of Ja v a and Peking. A fter th e photographs (republished also by S. Sergi) the sim ilarity of th e T ern ifin e probably m ale m andible also w ith the H eid elb erg m andible is evident, w hereas the second (fem ale ?) m andible, in its p ro file, rem inds, m orphologically, of m ore Pongid low er jaw s. C om parisons w ith m easurem ents of the H eidelberg m andible show th a t this specim en is som ew hat larg er b u t has sm aller teeth than the T ern ifin e m andibles. The new generic nam e “A tlanthropus” does not seem ju stified as w e do not know enough a b o u t th e v a ria b ility of the m andibles of the subgenus Homo (Pithecanthropus) as yet. T herefore the nam e H om o (Pithecanthropus) atlanticus or m auritanicus w ould b e tte r fit the taxonom y. Evidently, A ram bourg has a different concept of th e H om inid system .